PEMBELAJARAN PRA MEMBACA DENGAN MEDIA TRACING CARD UNTUK ANAK KELOMPOK A DI RA TUNAS MULIA DUA PANDANLANDUNG WAGIR KABUPATEN MALANG - Yulaika Nur Arrofi; Devi Wahyu Ertanti; Mutiara Sari Dewi (Jurnal Dewantara, 2022)
The government is trying to increase reading interest in Indonesia, one of which is by way of literacy movement since. In Indonesia the ability to read, write and count is one of the main academic goals.. For early childhood being able to read takes a very long time and. Tracing card is introducing pre-reading activities in a way that is fun for. This type ofresearch is qualitative research in the form of case studies. The source of this research data is group A in RA Tunas Mulia Dua. The results showed theuse of media tracing cards by the way children are invited to touch and trace the letters of the alphabet using the tips of the index and middle fingers, children feel rough and smooth surfaces with a light touch. Learning is tailored to the theme and learning plan designed by the teacher.